Ukuran Perusahaan Sebagai Pemoderasi Pengaruh Struktur Modal, Profitabilitas, Dan Islamic Social Reporting Terhadap Nilai Perusahaan Pada Bank Umum Syariah - Dessy Fitria; Nafis Irkhami (ITB AAS INDONESIA Surakarta, 2021)
This study aims to determine the size of the company as a derivative of the influence of capital structure, profitability, and islamic social reporting on firm value in islamic commercial banks in Indonesia. This type of research is a quantitative study with a population of islamic commercial banks registered with OJK. The sample method of this study used a purposive sampling method in which there was a sampling with certain considerations or criteria, so that the sample obtained was 60 samples from 12 islamic commercial banks with the 2015-2019 observation period. The type of data used is panel data. The analysis method used includes descriptive statistical test, stationarity test, multiple regression test, T test, F test, R2, classical assumption test and MRA test. The Moderated Regression Analysis (MRA) test uses data processing software Eviews. The results show that partially the capital structure variable has a negative and significant effect on firm value. Meanwhile, the profitability variable has a positive and significant impact on firm value. Then, the ISR variable has a positive and insignificant effect. Based on the Moderated Regression Analysis (MRA) test, it shows that the interaction of firm size cannot detect the effect of capital structure and profitability on firm value.